Positive electrode precursor

The positive electrode precursor, featuring a carbon material, oxidized coal, and an alkali metal compound with oxidized coal coating, enhances the thermal stability, capacity, and decomposition efficiency of alkali metal compounds in electricity storage devices, overcoming the challenges faced by existing technologies.

JP7662151B2Active Publication Date: 2025-04-15ASAHI KASEI KOGYO KABUSHIKI KAISHA +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021043271
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-04-15
Estimated Expiration
2041-03-17

AI Technical Summary

Technical Problem

Existing electricity storage devices, such as electric double layer capacitors and lithium-ion batteries, face challenges in achieving high energy density, high output characteristics, and high durability simultaneously, particularly at high temperatures.

Method used

A positive electrode precursor is developed, comprising a carbon material, oxidized coal, and an alkali metal compound, where oxidized coal is coated on the surface of the positive electrode active material and the alkali metal compound, enhancing thermal stability, capacity, and decomposition efficiency of alkali metal compounds.

Benefits of technology

The proposed solution provides a nonaqueous alkali metal power storage device with high thermal stability, increased capacity, and efficient decomposition of alkali metal compounds, addressing the limitations of existing devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662151000003
    Figure 0007662151000003
  • Figure 0007662151000004
    Figure 0007662151000004
  • Figure 0007662151000005
    Figure 0007662151000005
Patent Text Reader

Abstract

To provide a positive electrode precursor capable of providing a non-aqueous alkali metal storage element having high stability and high capacity and promoting decomposition of an alkali metal compound.SOLUTION: A positive electrode precursor includes a positive electrode active material containing a carbon material, a coal oxide, and an alkali metal compound other than the positive electrode active material. The positive electrode precursor includes a positive electrode current collector, and a positive electrode active material layer containing the positive electrode active material and the coal oxide and provided on one or both sides of the positive electrode current collector. At least a part of the surface of the positive electrode active material and at least a part of the surface of the alkali metal compound are coated with the coal oxide.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode precursor. [Background technology]

[0002] In recent years, from the viewpoint of the conservation of the global environment and the effective use of energy aimed at resource saving, attention has been drawn to power smoothing systems or midnight power storage systems for wind power generation, distributed household power storage systems based on solar power generation technology, power storage systems for electric vehicles, and the like. The first requirement for batteries used in these power storage systems is high energy density. As a promising candidate for a high energy density battery that can meet such requirements, the development of lithium ion batteries has been vigorously pursued. The second requirement is high output characteristics. For example, in a combination of a high-efficiency engine and a power storage system (e.g., a hybrid electric vehicle) or a combination of a fuel cell and a power storage system (e.g., a fuel cell electric vehicle), a power storage system that exhibits high output discharge characteristics during acceleration is required. Currently, electric double layer capacitors, nickel-metal hydride batteries, and the like have been developed as high-output power storage devices.

[0003] Among electric double layer capacitors, those that use activated carbon for the electrodes have output characteristics of about 0.5 to 1 kW / L. This electric double layer capacitor not only has high output characteristics, but also has high durability (cycle characteristics and high-temperature storage characteristics), and has been considered to be the optimal device for the above-mentioned fields that require high output. However, since its energy density is only about 1 to 5 Wh / L, further improvement of the energy density is necessary.

[0004] Nickel-metal hydride batteries, which are currently commonly used in hybrid electric vehicles, have high output equivalent to that of electric double-layer capacitors and an energy density of about 160 Wh / L. However, vigorous research is being conducted to further improve their energy density and output characteristics, as well as to increase their durability (especially their stability at high temperatures).

[0005] Research is also being conducted on lithium-ion batteries to increase their output. For example, lithium-ion batteries have been developed that can obtain high output exceeding 3kW / L at a discharge depth (i.e., the ratio (%) of the discharge amount to the discharge capacity of the storage element) of 50%. However, their energy density is 100Wh / L or less, and the design deliberately suppresses the high energy density that is the greatest feature of lithium-ion batteries. In addition, their durability (cycle characteristics and high-temperature storage characteristics) is inferior to that of electric double-layer capacitors, so such lithium-ion batteries are used in a discharge depth range narrower than 0 to 100% in order to provide practical durability. Since the capacity of lithium-ion batteries that can actually be used is even smaller, research is being actively conducted to further improve their durability.

[0006] As described above, there is a strong demand for practical use of an energy storage element that combines high energy density, high output characteristics, and high durability. However, since the above-mentioned existing energy storage elements each have their own advantages and disadvantages, a new energy storage element that satisfies these technical requirements is required. As a promising candidate, an energy storage element called a lithium ion capacitor has attracted attention and is being actively developed. A lithium ion capacitor is a type of energy storage element that uses a non-aqueous electrolyte solution containing lithium salt (hereinafter also referred to as a "non-aqueous alkali metal energy storage element"), and is an energy storage element that performs charging and discharging by a non-Faraday reaction due to the adsorption and desorption of anions at a positive electrode at about 3V or more, similar to an electric double layer capacitor, and a Faraday reaction due to the absorption and release of lithium ions at the negative electrode, similar to a lithium ion battery.

[0007] To summarize the electrode materials generally used in the above-mentioned energy storage elements and their characteristics, generally, when materials such as activated carbon are used for the electrodes and charging and discharging is performed by the adsorption and desorption of ions on the surface of the activated carbon (non-Faraday reaction), high output and high durability are obtained, but the energy density is low (for example, 1x). On the other hand, when oxide or carbon materials are used for the electrodes and charging and discharging is performed by the Faradaic reaction, the energy density is high (for example, 10x that of the non-Faraday reaction using activated carbon), but there are issues with durability and output characteristics.

[0008] As a combination of these electrode materials, electric double layer capacitors use activated carbon (energy density x1) for the positive and negative electrodes, and are characterized by the fact that both the positive and negative electrodes are charged and discharged through non-Faradic reactions. As such, they have high output and high durability, but are characterized by a low energy density (positive electrode x1 x negative electrode = 1).

[0009] Lithium-ion secondary batteries use lithium transition metal oxides (10 times the energy density) for the positive electrode and carbon materials (10 times the energy density) for the negative electrode, and are characterized by charging and discharging both the positive and negative electrodes through the Faraday reaction, and therefore have a high energy density (10 times the positive electrode x 10 times the negative electrode = 100), but have issues with output characteristics and durability. Furthermore, in order to satisfy the high durability required for hybrid electric vehicles, etc., the depth of discharge must be limited, and lithium-ion secondary batteries can only use 10 to 50% of the energy.

[0010] Lithium ion capacitors use activated carbon (energy density x1) for the positive electrode and carbon material (energy density x10) for the negative electrode, and are characterized by charging and discharging through a non-Faradic reaction at the positive electrode and a Faradic reaction at the negative electrode, making them an asymmetric capacitor that combines the characteristics of electric double layer capacitors and lithium ion secondary batteries. Lithium ion capacitors are characterized by their high output and durability, as well as their high energy density (1x positive electrode x 10x negative electrode = 10), and by the fact that there is no need to limit the depth of discharge like lithium ion secondary batteries.

[0011] Various studies have been conducted on further increasing the capacity of the lithium ion capacitor and on the development of new carbon materials (Patent Documents 1 to 3, Non-Patent Document 1). Patent Document 1 discloses a lithium ion capacitor containing activated carbon and graphene oxide (GO), and the binding force between active material particles can be increased by performing a reduction treatment on the graphene oxide in the positive electrode active material layer. Patent Document 2 proposes a high-capacity and high-output positive electrode precursor that promotes the decomposition of an alkali metal compound contained in the positive electrode precursor. Patent Document 3 discloses the use of oxidized coal (CO), which shows excellent proton conductivity even at high temperatures of 100°C or higher and does not exhibit electronic conductivity, as a solid electrolyte membrane. Non-Patent Document 1 discloses that pseudocapacity is expressed by the reaction of functional groups such as carbonyl groups on carbon with lithium ions. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2013-47171 A [Patent Document 2] International Publication No. 2017 / 126687 [Patent Document 3] JP 2017-52667 A [Non-patent literature]

[0013] [Non-Patent Document 1] Bor Z.Jag,Chenguang Liu,David Neff,Zhenning Yu,Ming C.Wang,Wei Xiong,Aruna Zhamu Nano Lett.,2011,11,3785-3791 [Non-Patent Document 2] EP Barrett, LG Joyner and P. Halenda, J. Am. Chem. Soc., 73, 373 (1951) [Non-Patent Document 3] BCLippens, J. Hde Boer, J. Catalysis, 4319 (1965) [Non-Patent Document 4] RS Mikhail, S. Brunauer, EE Bodor, J. Colloid Interface Sci., 26, 45 (1968) Summary of the Invention [Problem to be solved by the invention]

[0014] However, because graphene oxide contains many epoxy groups with low thermal stability, the functional groups are reductively decomposed in environments above 100°C. Therefore, when activated carbon and graphene oxide are mixed to improve the energy density, the functional groups of graphene oxide are decomposed when the activated carbon is vacuum-dried in a high-temperature environment of 100°C or higher to remove the moisture from the activated carbon, making it impossible to increase the capacity. In addition, there is room for improvement in increasing the capacity by using oxidized coal in combination with activated carbon, and in the decomposition efficiency of alkali metal compounds when oxidized coal is used in combination with alkali metal compounds.

[0015] An object of the present disclosure is to provide a positive electrode precursor that can provide a nonaqueous alkali metal electricity storage element that has high thermal stability and high capacity, and in which decomposition of an alkali metal compound is promoted. [Means for solving the problem]

[0016] Examples of embodiments of the present disclosure are listed below. [1] A positive electrode precursor comprising a positive electrode active material including a carbon material, oxidized coal, and an alkali metal compound other than the positive electrode active material, the positive electrode precursor includes a positive electrode current collector and a positive electrode active material layer including the positive electrode active material and the oxidized coal, the positive electrode active material layer being provided on one or both surfaces of the positive electrode current collector; A positive electrode precursor, in which at least a portion of a surface of the positive electrode active material and at least a portion of a surface of the alkali metal compound are covered with the oxidized coal. [2] 2. The positive electrode precursor according to item 1, wherein the content of the oxidized coal contained in the positive electrode active material layer of the positive electrode precursor is 0.5% by mass or more and 8.0% by mass or less, based on the total mass of the positive electrode active material layer, and the content of the alkali metal compound is 20.0% by mass or more and 45.0% by mass or less, based on the total mass of the positive electrode active material layer. [3] 3. The positive electrode precursor according to item 1 or 2, wherein the oxidized coal has a carboxyl functional group content of 10.0 atm% or more and 26.0 atm% or less, and an epoxy functional group content of 0.1 atm% or more and 8.0 atm% or less, as measured by XPS (X-ray photoelectron spectroscopy). [4] 4. The positive electrode precursor according to any one of items 1 to 3, wherein the sheet size of the oxidized coal measured by AFM (atomic force microscope) is 10 nm or more and less than 50 nm. Effect of the Invention

[0017] According to the present disclosure, there is provided a positive electrode precursor capable of providing a non-aqueous alkali metal electricity storage element that has high-temperature stability at or above 100° C., has a high capacity, and promotes decomposition of an alkali metal compound. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is an AFM image of oxidized coal in the example. [Diagram 2] FIG. 2 is an XPS spectrum of the oxidized coal in the example. [Diagram 3] FIG. 3 is an XPS spectrum of graphene oxide in a comparative example. [Figure 4] FIG. 4 is an SeM image of positive electrode precursor 1 in Example 1 taken at a magnification of 5,000 times. [Diagram 5] FIG. 5 is an SeM image of positive electrode precursor 5 in Comparative Example 1 taken at a magnification of 5,000 times. [Figure 6] FIG. 6 is an SeM image of positive electrode precursor 6 in Comparative Example 2 taken at a magnification of 5,000 times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <<Non-aqueous alkali metal storage element>> A non-aqueous alkali metal storage element generally comprises a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte solution, which is a solution of alkali metal ions dissolved in an organic solvent.

[0020] <Positive electrode precursor (positive electrode)> As described later, the negative electrode is pre-doped with alkali metal ions during the assembly process of the nonaqueous alkali metal storage element. In this specification, the positive electrode before the alkali metal doping process is defined as a "positive electrode precursor" and the positive electrode after the alkali metal doping process is defined as a "positive electrode".

[0021] The positive electrode precursor of the present disclosure includes a positive electrode active material containing a carbon material, oxidized coal, and an alkali metal compound other than the positive electrode active material. At least a part of the surface of the positive electrode active material and at least a part of the surface of the alkali metal compound are coated with oxidized coal. The positive electrode after the alkali metal doping step includes the positive electrode active material containing a carbon material and oxidized coal, and may further include an alkali metal compound in addition to these.

[0022] [Cathode active material layer] In the positive electrode current collector and the positive electrode, the positive electrode active material layer contains a positive electrode active material containing a carbon material and oxidized coal. The positive electrode active material layer may contain optional components described below as necessary in addition to these.

[0023] (Cathode active material) The positive electrode active material preferably contains activated carbon, and may further contain, in addition to activated carbon, a conductive polymer, a lithium transition metal oxide, and the like.

[0024] When using activated carbon as the positive electrode active material, there are no particular restrictions on the type of activated carbon and its raw materials. However, in order to achieve both high input / output characteristics and high energy density, it is preferable to optimally control the pores of the activated carbon. Specifically, when the mesopore volume derived from pores with a diameter of 20 Å or more and 500 Å or less calculated by the BJH method is V1 (cm 3 / g), and the micropore volume derived from pores with a diameter of less than 20 Å calculated by the MP method is V2 (cm 3 / g), (1) For high input / output characteristics, activated carbon that satisfies 0.3 < V1 ≤ 0.8, and 0.5 ≤ V2 ≤ 1.0, and has a specific surface area measured by the BET method of 1,500 m 2 / g or more and 3,000 m 2 / g or less (hereinafter also referred to as activated carbon 1) is preferable. Also, (2) In order to obtain high energy density, activated carbon that satisfies 0.8 < V1 ≤ 2.5, and 0.8 < V2 ≤ 3.0, and has a specific surface area measured by the BET method of 2,300 m 2 / g or more and 4,000 m 2 / g or less (hereinafter also referred to as activated carbon 2) is preferable.

[0025] The BET specific surface area, mesopore volume, micropore volume, and average pore diameter of the active material are values ​​that can be determined by the following methods. The sample is vacuum dried at 200°C for 24 hours, and the adsorption and desorption isotherms are measured using nitrogen as the adsorbate. Using the adsorption side isotherms obtained here, the BET specific surface area is calculated by the BET multipoint method or BET single point method, the mesopore volume is calculated by the BJH method, and the micropore volume is calculated by the MP method. The BJH method is a calculation method generally used to analyze mesopores, and was proposed by Barrett, Joyner, Halenda, et al. (Non-Patent Document 1). The MP method refers to a method of determining the micropore volume, micropore area, and micropore distribution using the "t-plot method" (Non-Patent Document 2), and is a method devised by RS Mikhail, Brunauer, and Bodor (Non-Patent Document 3). The average pore diameter refers to the total pore volume per mass of a sample, which is obtained by measuring the equilibrium adsorption amount of nitrogen gas at liquid nitrogen temperature and under each relative pressure, divided by the above-mentioned BET specific surface area.

[0026] (activated carbon 1) The mesopore volume V1 of the activated carbon 1 is set to 0.3 cm in order to increase the input / output characteristics when the positive electrode material is incorporated into a power storage element. 3 / g. V1 is preferably 0.8 cm 3 / g or less. V1 is more preferably 0.35 cm 3 / g or more 0.7cm 3 / g or less, more preferably 0.4 cm 3 / g or more 0.6cm 3 / g or less. The micropore volume V2 of the activated carbon 1 is 0.5 cm 3 V2 is preferably 1.0 cm3 / g or more in order to reduce the bulk of the activated carbon, increase the density as an electrode, and increase the capacity per unit volume. 3 / g or less. V2 is more preferably 0.6 cm 3 / g or more 1.0cm 3 / g or less, more preferably 0.8 cm 3 / g or more 1.0cm 3 / g or less. The ratio (V1 / V2) of the mesopore volume V1 to the micropore volume V2 is preferably in the range of 0.3≦V1 / V2≦0.9. That is, from the viewpoint of increasing the ratio of the mesopore volume to the micropore volume to an extent that the decrease in the output characteristics can be suppressed while maintaining a high capacity, it is preferable that V1 / V2 is 0.3 or more. On the other hand, from the viewpoint of increasing the ratio of the micropore volume to the mesopore volume to an extent that the decrease in the capacity can be suppressed while maintaining a high output characteristic, it is preferable that V1 / V2 is 0.9 or less. A more preferable range of V1 / V2 is 0.4≦V1 / V2≦0.7, and an even more preferable range of V1 / V2 is 0.55≦V1 / V2≦0.7.

[0027] The average pore diameter of the activated carbon 1 is preferably 17 Å or more, more preferably 18 Å or more, and most preferably 20 Å or more, from the viewpoint of maximizing the output of the obtained electricity storage element. Also, from the viewpoint of maximizing the capacity, the average pore diameter of the activated carbon 1 is preferably 25 Å or less. The BET specific surface area of ​​the activated carbon 1 is 1,500 m 2 / g or more 3,000m 2 / g or less, and 1,500m 2 / g or more 2,500m 2 / g or less. BET specific surface area is preferably 1,500 m 2 / g or more, good energy density is easily obtained, while the BET specific surface area is 3,000 m 2 / g or less, there is no need to add a large amount of binder to maintain the strength of the electrode, and therefore the performance per volume of the electrode is improved.

[0028] The activated carbon 1 having the above-mentioned characteristics can be obtained, for example, by using the raw materials and processing method described below. The carbon source used as the raw material of the activated carbon 1 is not particularly limited. For example, plant-based raw materials such as wood, wood flour, coconut shells, by-products during pulp production, bagasse, and blackstrap molasses; fossil-based raw materials such as peat, lignite, brown coal, bituminous coal, anthracite, petroleum distillation residue components, petroleum pitch, coke, and coal tar; various synthetic resins such as phenolic resins, vinyl chloride resins, vinyl acetate resins, melamine resins, urea resins, resorcinol resins, celluloid, epoxy resins, polyurethane resins, polyester resins, and polyamide resins; synthetic rubbers such as polybutylene, polybutadiene, and polychloroprene; other synthetic wood, synthetic pulp, and carbonized products thereof. Among these raw materials, from the viewpoint of mass production and cost, plant-based raw materials such as coconut shells and wood flour, and carbonized products thereof are preferred, and coconut shell carbonized products are particularly preferred.

[0029] As a method of carbonization and activation to convert these raw materials into the activated carbon 1, known methods such as a fixed bed method, a moving bed method, a fluidized bed method, a slurry method, a rotary kiln method, etc. can be adopted. As a method of carbonizing these raw materials, a method of burning using an inert gas such as nitrogen, carbon dioxide, helium, argon, xenon, neon, carbon monoxide, combustion exhaust gas, or a mixed gas containing these inert gases as a main component and other gases at about 400 to 700 ° C. (preferably 450 to 600 ° C.) for about 30 minutes to 10 hours can be mentioned. As a method of activating the carbonized material obtained by the carbonization method described above, a gas activation method in which burning is performed using an activation gas such as water vapor, carbon dioxide, or oxygen is preferably used. Among these, a method of using water vapor or carbon dioxide as an activation gas is preferable. In this activation method, it is preferable to activate the obtained carbonized material by heating it to 800 to 1,000°C over 3 to 12 hours (preferably 5 to 11 hours, more preferably 6 to 10 hours) while supplying the activation gas at a rate of 0.5 to 3.0 kg / h (preferably 0.7 to 2.0 kg / h). Furthermore, prior to the activation treatment of the carbonized material described above, the carbonized material may be first activated. In this first activation, a method of firing the carbon material at a temperature of less than 900°C using an activation gas such as water vapor, carbon dioxide, or oxygen to perform gas activation can be preferably adopted. Activated carbon 1 can be produced by appropriately combining the firing temperature and firing time in the carbonization method described above with the activation gas supply amount, heating rate, and maximum activation temperature in the activation method.

[0030] The average particle diameter of the activated carbon 1 is preferably 2 to 20 μm. If the average particle diameter is 2 μm or more, the density of the active material layer is high, so the capacity per electrode volume tends to be high. A small average particle diameter may result in a drawback such as low durability, but if the average particle diameter is 2 μm or more, such a drawback is unlikely to occur. On the other hand, if the average particle diameter is 20 μm or less, it tends to be easily adapted to high-speed charging and discharging. The average particle diameter of the activated carbon 1 is more preferably 2 to 15 μm, and further preferably 3 to 10 μm.

[0031] (activated carbon 2) The mesopore volume V1 of the activated carbon 2 is set to 0.8 cm from the viewpoint of increasing the output characteristics when the positive electrode material is incorporated into an energy storage element. 3 It is preferable that V1 is a value larger than 2.5 cm / g from the viewpoint of suppressing a decrease in the capacity of the electric storage element. 3 / g or less. V1 is more preferably 1.00 cm 3 / g or more and 2.0 cm3 / g or less, more preferably 1.2 cm 3 / g or more 1.8cm 3 The micropore volume V2 of the activated carbon 2 is preferably a value greater than 0.8 cm3 / g in order to increase the specific surface area of ​​the activated carbon and the capacity. From the viewpoint of increasing the density of the activated carbon as an electrode and increasing the capacity per unit volume, V2 is preferably 3.0 cm3 / g or less. 3 / g or less. V2 is more preferably 1.0 cm 3 / g greater than 2.5cm 3 / g or less, more preferably 1.5 cm 3 / g or more 2.5cm 3 / g or less. The activated carbon 2 having the above-mentioned mesopores and micropores has a higher BET specific surface area than activated carbons used for conventional electric double layer capacitors or lithium ion capacitors. The specific value of the BET specific surface area of ​​the activated carbon 2 is 2,300 m 2 / g or more 4,000m 2 / g or less, and 2 / g or more 4,000m 2 / g or less is more preferable, and 3,200m 2 / g or more 3,800m 2 / g or less. 2 / g or more, good energy density is easily obtained, and the BET specific surface area is 4,000 m 2 / g or less, there is no need to add a large amount of binder to maintain the strength of the electrode, and therefore the performance per volume of the electrode is improved.

[0032] The activated carbon 2 having the above-mentioned characteristics can be obtained, for example, by using the raw materials and processing methods described below. The carbonaceous material used as the raw material of the activated carbon 2 is not particularly limited as long as it is a carbon source that is usually used as an activated carbon raw material, and examples thereof include plant-based raw materials such as wood, wood powder, and coconut shells; fossil-based raw materials such as petroleum pitch and coke; and various synthetic resins such as phenolic resin, furan resin, vinyl chloride resin, vinyl acetate resin, melamine resin, urea resin, and resorcinol resin. Among these raw materials, phenolic resin and furan resin are particularly preferred because they are suitable for producing activated carbon with a high specific surface area.

[0033] The method of carbonizing these raw materials or the heating method during activation treatment include known methods such as a fixed bed method, a moving bed method, a fluidized bed method, a slurry method, and a rotary kiln method. The atmosphere during heating is an inert gas such as nitrogen, carbon dioxide, helium, argon, or a gas containing these inert gases as the main component and other gases. The carbonization temperature is generally about 400 to 700°C and the calcination is performed for about 0.5 to 10 hours. The activation method of the charcoal includes a gas activation method in which the charcoal is calcined using an activation gas such as water vapor, carbon dioxide, or oxygen, and an alkali metal activation method in which the charcoal is mixed with an alkali metal compound and then heated, but the alkali metal activation method is preferred for producing activated carbon with a high specific surface area. In this activation method, the carbide and an alkali metal compound such as KOH or NaOH are mixed in a mass ratio of 1:1 or more (the amount of the alkali metal compound is equal to or more than the amount of the carbide), and then heated in an inert gas atmosphere at a temperature in the range of 600 to 900°C for 0.5 to 5 hours, and then the alkali metal compound is washed and removed with acid and water, and further dried. In order to increase the amount of micropores and not increase the amount of mesopores, it is preferable to mix a larger amount of carbide with KOH during activation. In order to increase both the amount of micropores and the amount of mesopores, it is preferable to use a larger amount of KOH. In addition, in order to mainly increase the amount of mesopores, it is preferable to perform steam activation after performing alkali activation treatment. The average particle size of the activated carbon 2 is preferably 2 μm or more and 20 μm or less. More preferably, it is 3 μm or more and 10 μm or less.

[0034] (Use of activated carbon) Activated carbons 1 and 2 may each be a single type of activated carbon or a mixture of two or more types of activated carbons, showing the respective characteristic values as a whole mixture. Either one of these activated carbons 1 and 2 may be selected and used, or both may be mixed and used. The positive electrode active material may contain materials other than activated carbons 1 and 2 (for example, activated carbons without the specific V1 and / or V2 described above, or materials other than activated carbons (for example, conductive polymers, etc.)). In an exemplary embodiment, the total content of activated carbons 1 and 2 is preferably 40.0% by mass or more and 70.0% by mass or less, more preferably 45.0% by mass or more and 65.0% by mass or less. If this value is 40.0% by mass or more, the energy density can be increased. If this value is 70.0% by mass or less, the high-temperature durability and high-voltage durability can be improved.

[0035] (Lithium transition metal oxide) The positive electrode active material layer preferably further contains a lithium transition metal compound. By including a lithium transition metal oxide, the non-aqueous alkali metal storage element can be made to have a higher capacity. The lithium transition metal oxide includes a transition metal oxide capable of occluding and releasing lithium. There is no particular limitation on the transition metal oxide used as the positive electrode active material. Examples of the transition metal oxide include oxides containing at least one element selected from the group consisting of cobalt, nickel, manganese, iron, vanadium, and chromium. Specifically, as the transition metal oxide, the following formula: Li x CoO2 {wherein x satisfies 0 ≦ x ≦ 1.}, Li x NiO2 {wherein x satisfies 0 ≦ x ≦ 1.}, Li x Ni y M (1-y) O2 {wherein M is at least one element selected from the group consisting of Co, Mn, Al, Fe, Mg, and Ti, x satisfies 0 ≦ x ≦ 1, and y satisfies 0.05 < y < 0.97.}, Li x Ni 1 / 3 Co 1 / 3 Mn1 / 3 O2 {where x satisfies 0 ≦ x ≦ 1.}, Li x MnO2 {where x satisfies 0 ≦ x ≦ 1.}, α-Li x FeO2 {where x satisfies 0 ≦ x ≦ 1.}, Li x VO2 {where x satisfies 0 ≦ x ≦ 1.}, Li x CrO2 {where x satisfies 0 ≦ x ≦ 1.}, Li x FePO4 {where x satisfies 0 ≦ x ≦ 1.}, Li x MnPO4 {where x satisfies 0 ≦ x ≦ 1.}, Li z V2(PO4)3 {where z satisfies 0 ≦ z ≦ 3.}, Li x Mn2O4 {where x satisfies 0 ≦ x ≦ 1.}, Li x M y Mn (2-y) O4 {where M is at least one element selected from the group consisting of Co, Mn, Al, Fe, Mg, and Ti, x satisfies 0 ≦ x ≦ 1, and y satisfies 0.05 < y < 0.97.}, Li x Ni a Co b Al (1-a-b) O2 {where x satisfies 0 ≦ x ≦ 1, and a and b satisfy 0.02 < a < 0.97 and 0.02 < b < 0.97.}, Li x Ni c Co d Mn (1-c-d) O2 {where x satisfies 0 ≦ x ≦ 1, and c and d satisfy 0.02 < c < 0.97 and 0.02 < d < 0.97.} Compounds represented by the like are exemplified. Among these, from the viewpoints of high capacity, low resistance, cycle characteristics, decomposition of the alkali metal compound, and suppression of the lack of the positive electrode active material during pre-doping, the above formula Li x Ni a Co b Al (1-a-b) O2, Lix Ni c Co d Mn (1-c-d) O2, Li x CoO2, Li x Mn2O4, or Li x FePO4, Li x MnPO4, and Li z Compounds represented by V2(PO4)3 are preferred.

[0036] If the positive electrode precursor contains an alkali metal compound different from the positive electrode active material, the alkali metal compound can be a dopant source for the alkali metal in pre-doping, and the negative electrode can be pre-doped. Therefore, even if the transition metal compound does not contain lithium ions in advance (i.e., x=0 or z=0), the non-aqueous alkali metal storage element can be electrochemically charged and discharged. The content of the lithium transition metal oxide in the positive electrode active material layer of the positive electrode precursor is preferably 8.0 mass% or more and 30.0 mass% or less. If the content of the lithium transition metal oxide is 8.0 mass% or more, the non-aqueous alkali metal storage element can have a high capacity. If the content of the lithium transition metal oxide is 30.0 mass% or less, the non-aqueous alkali metal storage element can have a low resistance.

[0037] (Oxidized coal) Oxidized coal is a carbon material obtained by oxidizing coal. Coal is classified into lignite, subbituminous coal, bituminous coal, and anthracite according to the degree of coalification, and anthracite is more preferably used. Anthracite is the most coalified coal, but classification standards and names according to the degree of coalification vary from country to country, and in JIS M 1002, coal with a fuel ratio of 4.0 or more is called anthracite. In this specification, coal is classified according to JIS, and in particular, anthracite follows the definition in JIS M 1002. Oxidized coal is characterized by mainly containing carboxyl groups and having few epoxy groups. The oxidized coal does not exhibit electrical conductivity even when heat treated at 100°C to 200°C.

[0038] (Graphene oxide) Graphene oxide is a carbon material obtained by oxidizing graphene or graphite. Graphene is a carbon material in which carbon atoms form a two-dimensional sheet structure. A single layer is classified as single-layer graphene, and a multi-layer is classified as multi-layer graphene. Graphite is classified as natural graphite or artificial graphite. Generally, graphene oxide is synthesized by oxidizing graphite using a strong acid solution such as sulfuric acid by the Hummers method, followed by separation and purification. During this oxidation process, a large number of epoxy groups are generated as oxygen-containing functional groups on the edge surfaces of graphene. Since epoxy groups have low thermal stability, oxygen is released by heating them to above 100°C or reducing them electrochemically, resulting in reduced graphene oxide (RGO). RGO is characterized by its high electronic conductivity because carbon is bonded by sp2 bonds, and is a carbon material different from oxidized coal.

[0039] The content of the oxidized coal in the positive electrode active material layer is preferably 0.5% by mass or more and 8.0% by mass or less, more preferably 1.0% by mass or more and 6.0% by mass or less, and particularly preferably 2.0% by mass or more and 5.0% by mass or less, based on the total mass of the positive electrode active material layer. If the content of the oxidized coal in the positive electrode active material layer is 0.5 or more, the capacity of the nonaqueous alkali metal storage element can be increased. If the content of the oxidized coal in the positive electrode active material layer is 8.0 or less, the aggregation of the oxidized coal can be suppressed and the capacity can be increased without excessively covering the surface of the positive electrode active material.

[0040] In the positive electrode precursor, the oxidized coal coats at least a part of the surface of the positive electrode active material and at least a part of the surface of the alkali metal compound. By coating the surface of the positive electrode active material with the oxidized coal, the carboxyl groups present on the surface of the oxidized coal are more likely to react with the alkali metal ions in the electrolyte, so that a high-capacity non-aqueous alkali metal storage element can be obtained. In addition, by coating the surface of the alkali metal compound with the oxidized coal, the acidic functional groups such as carboxyl groups present on the surface of the oxidized coal can promote the decomposition of the alkali metal compound and promote pre-doping into the negative electrode. In the positive electrode after pre-doping, it is preferable that at least a part of the surface of the positive electrode active material is coated with the oxidized coal, and when included, it is preferable that at least a part of the surface of the alkali metal compound is also coated with the oxidized coal.

[0041] Oxidized coal can be synthesized, for example, by oxidizing coal using the Hummers process in an aqueous solution containing sodium nitrate, sulfuric acid, potassium permanganate, and oxygen peroxide. The obtained oxidized coal can be washed with an aqueous hydrochloric acid solution and water, and then dried to obtain oxidized coal powder. The obtained oxidized coal powder can be dissolved in water, irradiated with ultrasound, and centrifuged to remove insoluble impurities, to obtain a colloidal solution of oxidized coal.

[0042] The size of the oxidized coal can be measured by the topology of the coal deposited on the mica: atomic force microscope (AFM). The sheet size (width) of the oxidized coal is preferably 1 nm or more and 100 nm or less, more preferably 5 nm or more and 50 nm or less, even more preferably 10 nm or more and less than 50 nm, and particularly preferably 10 nm or more and 30 nm or less. If the width of the oxidized coal is 1 nm or more, it has excellent dispersibility. If the width is 100 nm or less, it is possible to reduce the resistance by promoting the diffusion of ions. In addition, the height of the oxidized coal is preferably 0.2 nm or more and 20 nm or less, more preferably 0.4 nm or more and 15 nm or less, and even more preferably 0.6 nm or more and 10 nm or less. If the height is 0.2 nm or more, it has excellent dispersibility. If the height is 20 nm or less, it is possible to reduce the resistance by promoting the diffusion of ions.

[0043] The functional groups contained in the oxidized coal can be measured using X-ray photoelectron spectroscopy (XPS). In the obtained XPS spectrum, the peak at the C1s binding energy of 285 eV can be assigned to a C-C bond, the peak at 286 eV to a C-O bond, the peak at 287 eV to a C-O-C bond, and the peak at 289 eV to an O=C-O bond. In the oxidized coal in this embodiment, the amount of carboxyl groups assigned to the peak at 289 eV is 10.0 atm% or more and 26.0 atm% or less, and the amount of epoxy groups assigned to the peak at 287 eV is 0.1 atm% or more and 8.0 atm% or less. If the amount of carboxyl groups is 10.0 atm% or more, the oxidized coal has excellent dispersibility in the coating liquid and functions as an adsorption and desorption site for alkali metal ions, thereby enabling the non-aqueous alkali metal storage element to have a high capacity. If the amount of carboxyl groups is 26.0 atm% or less, the electronic conductivity of the oxidized coal is increased, enabling the output to be increased. If the amount of epoxy functional groups is 0.1 atm% or more, the dispersibility in the coating liquid can be improved. If the amount of epoxy functional groups is 8.0 atm% or less, the decomposition of the functional groups at high temperatures can be suppressed, and the thermal stability can be improved.

[0044] In general, epoxy and hydroxyl groups are likely to form on the basal plane of graphene, while carboxyl groups are likely to form on the edges. Graphite and graphene have mainly developed basal planes, so epoxy functional groups are likely to form through oxidation treatment, while coal has mainly developed amorphous structures, so carboxyl groups are likely to form through oxidation treatment. This is the difference between oxidized coal and graphene oxide, and is the reason why oxidized coal has high thermal stability (structural stability).

[0045] (alkali metal compounds) The positive electrode active material layer of the positive electrode precursor of the present disclosure contains an alkali metal compound other than the positive electrode active material. The alkali metal compound decomposes in the positive electrode precursor to release cations, and is reduced at the negative electrode, thereby pre-doping the negative electrode. The alkali metal compound may be contained in the positive electrode precursor in any manner. For example, the alkali metal compound may be present between the positive electrode collector and the positive electrode active material layer, may be present on the surface of the positive electrode active material layer, or may be present in the positive electrode active material layer. The alkali metal compound is preferably contained in the positive electrode active material layer formed on the positive electrode collector of the positive electrode precursor. In such an embodiment, vacancies are formed in the positive electrode active material layer with the pre-doping of the alkali metal ions to the negative electrode, and the effective area of ​​the positive electrode active material layer is increased. The positive electrode after pre-doping may also contain the alkali metal compound other than the positive electrode active material.

[0046] Examples of such alkali metal compounds include oxides such as MO, hydroxides such as MOH, halides such as MF and MCl, and carboxylates such as RCOOM (wherein R is H, an alkyl group, or an aryl group), with M being at least one selected from Li, Na, K, Rb, and Cs, and at least one of these may be used. Specific examples of the alkali metal compounds include lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, cesium carbonate, lithium oxide, and lithium hydroxide. As the alkali metal compound, at least one of alkali metal carbonates selected from lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, and cesium carbonate is preferably used, and lithium carbonate, sodium carbonate, or potassium carbonate is more preferably used, and lithium carbonate is particularly preferably used from the viewpoint of high capacity per unit mass.

[0047] The positive electrode precursor is required to contain at least one type of alkali metal compound. The positive electrode precursor may contain, in place of or in addition to the above-mentioned alkali metal compound, one or more types selected from carbonates, oxides, hydroxides, halides, and carboxylates of an alkaline earth metal selected from the group consisting of Be, Mg, Ca, Sr, and Ba.

[0048] The alkali metal compound and the alkaline earth metal compound, if used, are preferably in the form of fine particles. The average particle diameter of the alkali metal compound is preferably 0.1 μm or more and 10 μm or less. If the average particle diameter is 0.1 μm or more, the dispersibility in the positive electrode precursor is excellent. If the average particle diameter is 10 μm or less, the surface area of ​​the alkali metal compound increases, so the decomposition reaction proceeds efficiently. In addition, the average particle diameter of the alkali metal compound is preferably smaller than the average particle diameter of the activated carbon described above. If the average particle diameter of the alkali metal compound is smaller than the average particle diameter of the activated carbon, the electronic conductivity of the positive electrode active material layer increases, which can contribute to reducing the resistance of the electrode body or the storage element. There is no particular limit to the method for measuring the average particle diameter of the alkali metal compound in the positive electrode precursor, but it can be calculated from SEM images and SEM-EDX images of the cross section of the positive electrode. As for the method for forming the cross section of the positive electrode, BIB processing can be used, in which an Ar beam is irradiated from above the positive electrode and a smooth cross section is prepared along the edge of a shielding plate placed directly above the sample. Various methods can be used for finely granulating the alkali metal compound. For example, a grinding machine such as a ball mill, a bead mill, a ring mill, a jet mill, or a rod mill can be used.

[0049] The content (mass%) of the alkali metal compound contained in the positive electrode active material layer of the positive electrode precursor is preferably 20.0 mass% or more and 45.0 mass% or less when the total mass of the positive electrode active material layer is 100 mass%. If this value is 20.0 mass% or more, a sufficient amount of alkali metal ions can be pre-doped into the negative electrode, and the capacity of the non-aqueous alkali metal storage element is increased. If this value is 45.0 mass% or less, the electronic conductivity in the positive electrode precursor can be increased, so that the decomposition of the alkali metal compound can be efficiently performed. When the positive electrode precursor contains the above-mentioned two or more types of alkali metal compounds or alkaline earth metal compounds in addition to the alkali metal compounds, it is preferable that the total amount of the alkali metal compounds and the alkaline earth metal compounds is within the above range. The above-mentioned alkali metal elements and alkaline earth metal elements can be quantified by ICP-AES, atomic absorption spectrometry, fluorescent X-ray spectrometry, neutron activation analysis, ICP-MS, etc.

[0050] (Other components of the positive electrode active material layer) The positive electrode active material layer of the positive electrode precursor in the present invention may contain, in addition to the positive electrode active material, the oxidized coal, and the alkali metal compound, other components such as a dispersant, a conductive filler, a binder, and a pH adjuster, as necessary.

[0051] The dispersant is not particularly limited, but one or more selected from, for example, carboxymethylcellulose, polycarboxylic acid, polycarboxylate, polyvinylpyrrolidone, polyvinyl alcohol, and surfactants are preferably used. The dispersant particularly preferably contains, for example, carboxymethylcellulose and one or more selected from polyvinylpyrrolidone and polyvinyl alcohol. The content of the dispersant is preferably 0.1% by mass or more and 7.0% by mass or less with respect to 100% by mass of the solid content in the positive electrode active material layer of the positive electrode precursor. If the amount of the dispersant is 7.0% by mass or less, the ingress and egress of ions into and the diffusion of ions into the positive electrode active material are not hindered, and high input / output characteristics are expressed.

[0052] Examples of the binder that can be used include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), fluororubber, polyimide, latex, styrene-butadiene copolymer, acrylic copolymer, etc. The content of the binder in the positive electrode active material layer of the positive electrode precursor is preferably 0 to 20 mass%, more preferably 0.1 to 15 mass%, relative to 100 mass% of the positive electrode active material.

[0053] The conductive filler is preferably made of a conductive carbonaceous material having a higher conductivity than the positive electrode active material. As such a conductive filler, for example, one or more selected from carbon black, graphite, graphene, carbon nanotubes, etc., and mixtures thereof are preferable. As carbon black, for example, ketjen black and acetylene black, etc. are exemplified. As graphite, for example, scaly graphite, etc. are exemplified. As the conductive filler, carbon black is particularly preferably used. The content of the conductive filler in the positive electrode active material layer of the positive electrode precursor is preferably 25% by mass or less, more preferably in the range of 5% by mass or more and 20% by mass or less, relative to 100% by mass of the positive electrode active material. From the viewpoint of increasing input, it is preferable to mix the conductive filler into the positive electrode active material layer, but it is preferable to keep the content at 25% by mass or less from the viewpoint of maintaining the energy density per volume of the storage element.

[0054] When water is used as a solvent for the coating liquid for forming the positive electrode active material layer, the coating liquid may become alkaline by adding an alkali metal compound. Therefore, a pH adjuster may be added to the coating liquid for forming the positive electrode active material layer as necessary. The pH adjuster is not particularly limited, but examples thereof include hydrogen halides such as hydrogen fluoride, hydrogen chloride, and hydrogen bromide; halogen oxo acids such as hypochlorous acid, chlorous acid, and chloric acid; carboxylic acids such as formic acid, acetic acid, citric acid, oxalic acid, lactic acid, maleic acid, and fumaric acid; sulfonic acids such as methanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid; and acids such as nitric acid, sulfuric acid, phosphoric acid, boric acid, and carbon dioxide.

[0055] [Positive electrode current collector] The material constituting the positive electrode current collector is not particularly limited as long as it has high electronic conductivity and does not deteriorate due to elution in the electrolyte or reaction with the electrolyte or ions, but metal foil is preferred. As the positive electrode current collector in the non-aqueous alkali metal storage element, aluminum foil is more preferred. The metal foil may be a normal metal foil without unevenness or through holes, or may be a metal foil with unevenness obtained by embossing, chemical etching, electrolytic deposition, blasting, or the like, or may be a metal foil with through holes such as expanded metal, punching metal, and etching foil. From the viewpoint of the alkali metal doping process described later, non-porous aluminum foil is more preferred, and it is particularly preferred that the surface of the aluminum foil is roughened. The thickness of the positive electrode current collector is not particularly limited as long as it can sufficiently maintain the shape and strength of the positive electrode, but for example, 1 to 100 μm is preferred. It is preferable to provide an anchor layer containing a conductive material such as graphite, flake graphite, carbon nanotubes, graphene, ketjen black, acetylene black, and vapor-grown carbon fiber on the surface of the metal foil. The provision of the anchor layer improves electrical conduction between the positive electrode current collector and the positive electrode active material layer, thereby enabling the resistance to be reduced. The thickness of the anchor layer is preferably 0.1 μm or more and 5 μm or less per side of the positive electrode current collector.

[0056] The thickness of the positive electrode active material layer is preferably 10 μm or more and 200 μm or less per side of the positive electrode current collector. The thickness of the positive electrode active material layer is more preferably 20 μm or more and 150 μm or less per side, and even more preferably 30 μm or more and 100 μm or less. If the thickness is 10 μm or more, sufficient charge / discharge capacity can be achieved. On the other hand, if the thickness is 200 μm or less, the ion diffusion resistance in the electrode can be kept low. Therefore, sufficient output characteristics can be obtained, and the cell volume can be reduced, and therefore the energy density can be increased. Note that the thickness of the positive electrode active material layer in the case where the positive electrode current collector has through holes or unevenness refers to the average value of the thickness per side of the part of the positive electrode current collector that does not have through holes or unevenness.

[0057] <Negative electrode> The negative electrode has a negative electrode current collector and a negative electrode active material layer provided on one or both sides of the negative electrode current collector.

[0058] [Negative electrode active material layer] The negative electrode active material layer contains a negative electrode active material, and may further contain optional components such as a dispersant, a conductive filler, and a binder, as necessary.

[0059] (Negative electrode active material) The negative electrode active material may be a material capable of absorbing and releasing alkali metal ions. Specific examples include carbon materials, titanium oxides, silicon, silicon oxides, silicon alloys, silicon compounds, tin, and tin compounds. The content of the negative electrode active material in the negative electrode active material layer of the negative electrode precursor is preferably 70% by mass or more, more preferably 80% by mass or more, based on the total mass of the negative electrode active material layer. The negative electrode active material is preferably in the form of particles.

[0060] The negative electrode active material preferably contains a carbon material. The content of the carbon material relative to the total amount of the negative electrode active material is preferably 50% by mass or more, more preferably 70% by mass or more. The content of the carbon material can be 100% by mass, but from the viewpoint of obtaining the effect of the combined use of other materials, it is preferably 95% by mass or less, and may be 90% by mass or less. The upper and lower limits of the range of the content of the carbon material can be arbitrarily combined.

[0061] Examples of carbon materials include non-graphitizable carbon materials; graphitizable carbon materials; carbon black; carbon nanoparticles; artificial graphite; natural graphite; graphitized mesophase carbon spheres; graphite whiskers; amorphous carbonaceous materials such as polyacene-based substances; carbonaceous materials obtained by heat treating carbon precursors such as petroleum-based pitch, coal-based pitch, mesocarbon microbeads, coke, and synthetic resins (e.g., phenolic resins); pyrolysates of furfuryl alcohol resins or novolac resins; fullerenes; carbon nanofibers; and composite carbon materials thereof.

[0062] Among these, from the viewpoint of reducing the resistance of the negative electrode, a composite carbon material is preferred in which one or more graphite materials selected from artificial graphite, natural graphite, graphitized mesophase carbon microspheres, graphite whiskers, and high specific surface area graphite are coexisted with one or more carbonaceous material precursors selected from petroleum-based pitch, coal-based pitch, mesocarbon microbeads, coke, and synthetic resins, such as phenolic resins, and the like, and the graphite material and the carbonaceous material derived from the carbonaceous material precursor are composited. The carbonaceous material precursor is not particularly limited as long as it becomes a carbonaceous material by heat treatment, but petroleum-based pitch or coal-based pitch is particularly preferred. Before the heat treatment, the graphite material and the carbonaceous material precursor may be mixed at a temperature higher than the melting point of the carbonaceous material precursor. The heat treatment temperature may be any temperature at which the components generated by volatilization or thermal decomposition of the carbonaceous material precursor used become carbonaceous materials, and is preferably from 400° C. to 2,500° C., more preferably from 500° C. to 2,000° C., and even more preferably from 550° C. to 1,500° C. The atmosphere in which the heat treatment is performed is not particularly limited, but a non-oxidizing atmosphere is preferred.

[0063] (Other components of the negative electrode active material layer) The negative electrode active material layer may contain optional components such as a dispersant, a binder, and a conductive filler, in addition to the negative electrode active material, as necessary. The dispersant, the conductive filler, and the binder in the negative electrode active material layer may be appropriately selected from the above-mentioned examples of the dispersant, the conductive filler, and the binder in the positive electrode active material layer of the positive electrode precursor. The content of the dispersant and the binder in the negative electrode active material layer may be within the above-mentioned ranges as the content of the dispersant and the binder in the positive electrode active material of the positive electrode precursor, respectively.

[0064] [Negative electrode current collector] The material constituting the negative electrode current collector is preferably a material that has high electronic conductivity and does not dissolve in the electrolyte or deteriorate due to reaction with the electrolyte or ions, and may be, for example, a metal foil. Such metal foil is not particularly limited, and examples thereof include aluminum foil, copper foil, nickel foil, and stainless steel foil. As the negative electrode current collector in the non-aqueous alkali metal storage element, when the non-aqueous electrolyte contains lithium ions, copper foil is preferable, and when the non-aqueous electrolyte uses an electrolyte consisting of sodium ions or potassium ions, aluminum foil is preferable. The metal foil as the negative electrode current collector may be a normal metal foil that does not have unevenness or through holes, or may be a metal foil having unevenness that has been embossed, chemically etched, electrolytic deposition, blasted, or the like, or may be a metal foil having through holes such as expanded metal, punching metal, and etching foil. The thickness of the negative electrode current collector is not particularly limited as long as it can sufficiently maintain the shape and strength of the negative electrode, and is, for example, 1 to 100 μm.

[0065] The thickness of the negative electrode active material layer is preferably 10 μm or more and 100 μm or less per side, more preferably 15 μm or more and 80 μm or less. If the thickness is 10 μm or more, good charge / discharge capacity can be achieved. On the other hand, if the thickness is 100 μm or less, the cell volume can be reduced, so that the energy density can be increased. When the negative electrode current collector has holes, the thickness of the negative electrode active material layer refers to the average thickness per side of the portion of the negative electrode current collector that does not have holes.

[0066] <Separator> The positive electrode precursor and the negative electrode are laminated with a separator interposed therebetween, or laminated and wound to form an electrode laminate or an electrode wound body having the positive electrode precursor, the negative electrode, and the separator. As the separator, a polyethylene microporous film or a polypropylene microporous film used in a lithium ion secondary battery, or a cellulose nonwoven paper used in an electric double layer capacitor, or the like, can be used. A film made of organic or inorganic fine particles may be laminated on one or both sides of these separators. In addition, organic or inorganic fine particles may be contained inside the separator. The thickness of the separator is preferably 5 μm or more and 35 μm or less. By making the thickness 5 μm or more, self-discharge due to internal micro-short tends to be small, which is preferable. On the other hand, by making the thickness 35 μm or less, the output characteristics of the storage element tend to be high, which is preferable. In addition, the thickness of the film made of organic or inorganic fine particles is preferably 1 μm or more and 10 μm or less. By making the thickness 1 μm or more, self-discharge due to internal micro-short tends to be small, which is preferable. On the other hand, a thickness of 10 μm or less is preferable because it tends to improve the output characteristics of the electricity storage element.

[0067] <Exterior body> As the exterior body, a metal can, a laminate film, etc. can be used. As the metal can, one made of aluminum is preferable. The metal can may be, for example, rectangular, round, cylindrical, etc. As the laminate film, a film in which a metal foil and a resin film are laminated is preferable, and a three-layer structure consisting of an outer layer resin film / metal foil / interior resin film is exemplified. The outer layer resin film is for preventing the metal foil from being damaged by contact, etc., and resins such as nylon or polyester can be suitably used. The metal foil is for preventing the permeation of moisture and gas, and foils such as copper, aluminum, and stainless steel can be suitably used. In addition, the interior resin film is for protecting the metal foil from the electrolyte stored inside and for melt sealing when the exterior body is heat-sealed, and polyolefin, acid-modified polyolefin, etc. can be suitably used.

[0068] <Electrolyte> The electrolyte is a non-aqueous electrolyte. That is, the electrolyte contains a non-aqueous solvent. The non-aqueous electrolyte contains 0.5 mol / L or more of an alkali metal salt based on the total amount of the non-aqueous electrolyte. That is, the non-aqueous electrolyte contains an alkali metal salt as an electrolyte. Examples of the non-aqueous solvent contained in the non-aqueous electrolyte include cyclic carbonates such as ethylene carbonate and propylene carbonate, and chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0069] As electrolyte salts containing alkali metal ions that dissolve in non-aqueous solvents, for example, MFSI, MBF4, MPF6, MClO4, LiB(C2O4)2, LiBF2(C2O4), etc. can be used, where M is Li, Na, K, Rb, or Cs. The non-aqueous electrolyte may contain at least one alkali metal ion, and may contain two or more alkali metal salts, or may contain an alkali metal salt and an alkaline earth metal salt selected from a beryllium salt, a magnesium salt, a calcium salt, a strontium salt, and a barium salt. When the non-aqueous electrolyte contains two or more alkali metal salts, the presence of cations with different Stokes radii in the non-aqueous electrolyte can suppress an increase in viscosity at low temperatures, improving the low-temperature characteristics of the non-aqueous alkali metal storage element. When the non-aqueous electrolyte contains an alkaline earth metal ion other than the alkali metal ion, the non-aqueous alkali metal storage element can be made to have a high capacity.

[0070] The method of incorporating the above-mentioned two or more kinds of alkali metal salts in the non-aqueous electrolyte solution, or the method of incorporating the alkali metal salt and the alkaline earth metal salt in the non-aqueous electrolyte solution, is not particularly limited, but examples thereof include a method of dissolving an alkali metal salt consisting of two or more kinds of alkali metal ions in the non-aqueous electrolyte solution in advance, and a method of dissolving an alkali metal salt and an alkaline earth metal salt in the non-aqueous electrolyte solution in advance. In addition, the positive electrode precursor may contain a compound represented by the following formula, in which M is one or more selected from Li, Na, K, Rb, and Cs: Carbonates such as M2CO3; Oxides such as MO; Hydroxides such as MOH; Halides such as MF and MCl; Carboxylate salts such as RCOOM, where R is H, an alkyl group, or an aryl group; and Alkaline earth metal carbonates selected from BeCO3, MgCO3, CaCO3, SrCO3, and BaCO3, as well as alkaline earth metal oxides, alkaline earth metal hydroxides, alkaline earth metal halides, and alkaline earth metal carboxylates. and the like, and decomposed in a pre-doping step described later.

[0071] The electrolyte salt concentration in the electrolytic solution is preferably in the range of 0.5 to 2.0 mol / L. At an electrolyte salt concentration of 0.5 mol / L or more, anions are sufficiently present, and the capacity of the nonaqueous alkali metal storage element is maintained. On the other hand, at an electrolyte salt concentration of 2.0 mol / L or less, the salt is sufficiently dissolved in the electrolytic solution, and the appropriate viscosity and conductivity of the electrolytic solution are maintained. When the nonaqueous electrolytic solution contains two or more types of alkali metal salts, or when the nonaqueous electrolytic solution contains an alkali metal salt and an alkaline earth metal salt, the total value of the salt concentrations is preferably 0.5 mol / L or more, and more preferably in the range of 0.5 to 2.0 mol / L.

[0072] The amount of water contained in the non-aqueous electrolyte is preferably 0 ppm or more and 500 ppm or less. If the amount of water is 0 ppm or more, the alkali metal compound in the positive electrode precursor can be slightly dissolved, so that pre-doping can be performed under mild conditions, resulting in high capacity and low resistance. If the amount of water is 500 ppm or less, the decomposition of the electrolyte is suppressed, thereby improving high-temperature storage characteristics. The amount of water in the electrolyte can be measured by the above-mentioned Karl Fischer method.

[0073] <<Method for producing a non-aqueous alkali metal storage element>> The non-aqueous alkali metal storage element of the present disclosure can be manufactured by assembling a storage element using a positive electrode precursor, a negative electrode, a separator, an exterior body, and a non-aqueous electrolyte solution, and then applying a voltage between the positive electrode precursor and the negative electrode to perform pre-doping. Each step will be described below.

[0074] [Production of positive electrode precursor] The positive electrode precursor has a positive electrode active material layer on one or both sides of the positive electrode current collector. In a typical embodiment, the positive electrode active material layer is fixed to the positive electrode current collector. The positive electrode precursor can be manufactured by known manufacturing techniques for electrodes in lithium ion batteries, electric double layer capacitors, etc. For example, various materials including a positive electrode active material are dispersed or dissolved in water or an organic solvent to prepare a slurry-like coating liquid, and the coating liquid is applied to one or both sides of a positive electrode current collector to form a coating film, which is then dried to obtain a positive electrode precursor. The obtained positive electrode precursor may be pressed to adjust the film thickness or bulk density of the positive electrode active material layer.

[0075] The method for preparing the coating liquid is not particularly limited, but can be suitably carried out using a dispersing machine such as a homodisper, a multi-axis dispersing machine, a planetary mixer, a thin film rotating type high-speed mixer, or a rotation / revolution mixer. In order to obtain a coating liquid in a well-dispersed state, it is preferable to disperse the coating liquid at a peripheral speed of 1 m / s or more and 50 m / s or less. A peripheral speed of 1 m / s or more is preferable because various materials are well dissolved or dispersed. A peripheral speed of 50 m / s or less is preferable because various materials are not destroyed by heat or shear force due to dispersion, and re-aggregation is suppressed.

[0076] The method of coating the surface of the positive electrode active material and the alkali metal compound with the oxidized coal is not particularly limited. From the viewpoint of more uniform coating, a method is preferred in which the oxidized coal is dispersed in water in advance to prepare an oxidized coal dispersion, and the oxidized coal dispersion is added to a coating liquid separately prepared from the positive electrode active material, the alkali metal compound, a dispersant, a binder, etc. The reason is that if the oxidized coal is not prepared as an oxidized coal dispersion, aggregation is likely to occur, and if the positive electrode active material and the oxidized coal dispersion are mixed first, the oxidized coal may be adsorbed onto the positive electrode active material.

[0077] The degree of dispersion of the coating liquid is preferably 0.1 μm or more and 100 μm or less as measured by a particle gauge. The upper limit of the degree of dispersion is more preferably 80 μm or less, and even more preferably 50 μm or less as measured by a particle gauge. If the particle size is within this range, the material is not crushed during preparation of the coating liquid, and clogging of the nozzle during coating and generation of streaks in the coating film are suppressed, allowing stable coating.

[0078] The viscosity (ηb) of the coating liquid is preferably 100 mPa·s to 4,000 mPa·s, more preferably 200 mPa·s to 2,000 mPa·s, and even more preferably 300 mPa·s to 1,500 mPa·s. If the viscosity (ηb) is 100 mPa·s or more, dripping during coating film formation is suppressed, and the width and thickness of the coating film can be well controlled. If the viscosity is 4,000 mPa·s or less, the dispersibility of the oxidized coal in the coating liquid is improved, and the oxidized coal can be uniformly coated on the surfaces of the positive electrode active material and the alkali metal storage element.

[0079] The TI value (thixotropy index value) of the coating liquid is preferably 1.1 or more, more preferably 1.2 or more, and further preferably 1.5 or more. If the TI value is 1.1 or more, the coating width and thickness can be well controlled.

[0080] The coating film of the positive electrode active material layer is not particularly limited, but a coating machine such as a die coater, a comma coater, a knife coater, or a gravure coater can be preferably used. The coating film may be formed by single-layer coating, or may be formed by multi-layer coating. In the case of multi-layer coating, the coating liquid composition may be adjusted so that the content of the components in each layer of the coating film is different. When applying the coating film on the positive electrode current collector, it may be multi-line coating, intermittent coating, or multi-line intermittent coating. When forming the positive electrode active material layer on both sides of the positive electrode current collector, it may be coated on one side of the positive electrode current collector, dried, and then coated on the other side and dried, in a sequential coating, or it may be coated on both sides of the positive electrode current collector at the same time, in a simultaneous double-sided coating, in which the coating liquid is applied and dried. In this case, the difference in thickness between the positive electrode active material layers on the front and back sides of the positive electrode current collector is preferably 10% or less of the average thickness of both. The closer the mass ratio and film thickness ratio of the positive electrode active material layer on the front and back surfaces is to 1.0, the less the charge / discharge load is concentrated on one surface, improving the high-load charge / discharge cycle characteristics.

[0081] After forming a coating film of the positive electrode active material layer on the positive electrode current collector, the coating film is dried. The coating film of the positive electrode precursor is preferably dried by an appropriate drying method such as hot air drying or infrared (IR) drying, preferably by far infrared rays, near infrared rays, or hot air. The coating film may be dried at a single temperature, or may be dried by changing the temperature in multiple stages. A combination of multiple drying methods may be used. The drying temperature is preferably 25°C or higher and 200°C or lower, more preferably 40°C or higher and 180°C or lower, and even more preferably 50°C or higher and 160°C or lower. If the drying temperature is 25°C or higher, the solvent in the coating film can be sufficiently volatilized. On the other hand, if the drying temperature is 200°C or lower, the coating film can be cracked due to sudden solvent volatilization, uneven distribution of the binder due to migration, and oxidation of the positive electrode current collector or the positive electrode active material layer can be suppressed.

[0082] The amount of moisture contained in the positive electrode active material layer after drying is preferably 0.1% by mass or more and 10% by mass or less when the total mass of the positive electrode active material layer is 100% by mass. If the amount of moisture is 0.1% by mass or more, deterioration of the binder due to excessive drying can be suppressed, and the resistance can be reduced. If the amount of moisture is 10% by mass or less, deactivation of alkali metal ions can be suppressed, and the capacity can be increased. When N-methyl-2-pyrrolidone (NMP) is used to adjust the coating liquid, the content of NMP in the positive electrode active material layer after drying is preferably 0.1% by mass or more and 10% by mass or less when the total mass of the positive electrode active material layer is 100%. The amount of moisture contained in the positive electrode active material layer can be measured, for example, by Karl Fischer titration (JIS 0068 (2001) "Method for measuring moisture in chemical products"). The amount of NMP contained in the positive electrode active material layer can be quantified by immersing the positive electrode active material layer in ethanol having a mass that is 50 to 100 times the mass of the positive electrode active material layer for 24 hours in a 25°C environment to extract NMP, and then measuring with GC / MS based on a calibration curve created in advance.

[0083] For pressing the positive electrode active material layer, a suitable press machine such as a hydraulic press machine, a vacuum press machine, or a roll press machine can be used. The thickness, bulk density, and electrode strength of the positive electrode active material layer can be adjusted by the press pressure, the gap between the press rolls, and the surface temperature of the press part, which will be described later. The press pressure is preferably 0.5 kN / cm or more and 20 kN / cm or less, more preferably 1 kN / cm or more and 10 kN / cm or less, and even more preferably 2 kN / cm or more and 7 kN / cm or less. If the press pressure is 0.5 kN / cm or more, the electrode strength can be sufficiently high. On the other hand, if the press pressure is 20 kN / cm or less, the positive electrode precursor does not bend or wrinkle, and the positive electrode active material layer can be adjusted to a desired thickness or bulk density. When a roll press machine is used for pressing, the gap between the press rolls can be set to an appropriate value so that the positive electrode active material layer has a desired thickness and bulk density. The press speed can be set to an appropriate speed at which the positive electrode precursor does not bend or wrinkle.

[0084] The surface temperature of the press part may be room temperature, or may be heated as necessary. The lower limit of the surface temperature of the press part when heated is preferably 60°C minus the melting point of the binder used, more preferably 45°C minus the melting point of the binder, and even more preferably 30°C minus the melting point of the binder. On the other hand, the upper limit of the surface temperature of the press part when heated is preferably 50°C plus the melting point of the binder used, more preferably 30°C plus the melting point of the binder, and even more preferably 20°C plus the melting point of the binder. For example, when polyvinylidene fluoride (melting point 150°C) is used as the binder, it is preferable to heat the press part to 90°C to 200°C, more preferably 105°C to 180°C, and even more preferably 120°C to 170°C. In addition, when a styrene-butadiene copolymer (melting point 100°C) is used as the binder, it is preferable to heat the press part to 40°C or more and 150°C or less, more preferably 55°C or more and 130°C or less, and even more preferably 70°C or more and 120°C or less. The melting point of the binder can be determined from the endothermic peak position of DSC (Differential Scanning Calorimetry). For example, using a PerkinElmer differential scanning calorimeter "DSC7", 10 mg of sample resin is set in a measurement cell, and the temperature is raised from 30°C to 250°C at a heating rate of 10°C / min in a nitrogen gas atmosphere. The endothermic peak temperature in the heating process is the melting point.

[0085] Pressing may be performed multiple times while changing the conditions of the pressing pressure, gap, speed, and surface temperature of the pressing part. When the positive electrode active material layer is applied in multiple stripes, it is preferable to slit it before pressing. If the positive electrode precursor is pressed without slitting the negative electrode active material layer applied in multiple stripes, excessive stress may be applied to the positive electrode current collector part not coated with the positive electrode active material layer, causing wrinkles. After pressing, the positive electrode active material layer may be slit again.

[0086] [Production of negative electrodes] The negative electrode of the non-aqueous alkali metal storage element can be manufactured by known electrode manufacturing techniques for lithium ion batteries, electric double layer capacitors, etc. For example, the negative electrode active material and other optional components used as necessary are dispersed or dissolved in water or an organic solvent to prepare a slurry-like coating liquid, and the coating liquid is applied to one or both sides of a negative electrode current collector to form a coating film, which is then dried to obtain a negative electrode. Furthermore, the obtained negative electrode may be pressed to adjust the film thickness or bulk density of the negative electrode active material layer. The preparation of the coating liquid for forming the negative electrode active material layer, the application of the coating liquid to the negative electrode current collector, the drying of the coating film, and the pressing can each be performed in accordance with the method described above for the production of the positive electrode precursor.

[0087] [Assembly process] In the assembly process, for example, a positive electrode terminal and a negative electrode terminal are connected to a laminate obtained by stacking a positive electrode precursor and a negative electrode cut into a sheet shape with a separator interposed therebetween to prepare an electrode laminate. Alternatively, a positive electrode terminal and a negative electrode terminal may be connected to a wound body obtained by stacking and winding a positive electrode precursor and a negative electrode with a separator interposed therebetween to prepare an electrode wound body. The shape of the electrode wound body may be cylindrical or flat. The method for connecting the positive electrode terminal and the negative electrode terminal is not particularly limited, but methods such as resistance welding and ultrasonic welding can be used. It is preferable to dry the electrode body (electrode laminate or electrode wound body) to which the terminals are connected to remove the remaining solvent. The drying method is not limited, but it can be dried by vacuum drying or the like. The remaining solvent is preferably 1.5 mass% or less per total mass of the positive electrode active material layer or the negative electrode active material layer. If the remaining solvent is more than 1.5 mass%, the solvent remains in the system and deteriorates the self-discharge characteristics, which is not preferable. The dried electrode body is preferably stored in an exterior body such as a metal can or a laminate film in a dry environment with a dew point of -40°C or less, and is preferably sealed except for one opening for injecting a non-aqueous electrolyte. If the dew point is higher than -40°C, moisture will adhere to the electrode body, and water will remain in the system, which is undesirable as it will deteriorate the self-discharge characteristics. The method for sealing the exterior body is not particularly limited, but methods such as heat sealing and impulse sealing can be used.

[0088] [Injection, impregnation, sealing process] After the assembly process, the non-aqueous electrolyte is injected into the electrode body housed in the exterior body. After the injection, it is desirable to further impregnate the positive electrode, the negative electrode, and the separator so that they are sufficiently soaked with the non-aqueous electrolyte. In a state where the electrolyte is not soaked in at least a part of the positive electrode, the negative electrode, and the separator, the alkali metal doping proceeds unevenly in the alkali metal doping process described later, so that the resistance of the obtained non-aqueous alkali metal storage element increases or the durability decreases. The impregnation method is not particularly limited, but for example, the electrode body after the injection is placed in a reduced pressure chamber with the exterior body open, and the chamber is reduced pressure using a vacuum pump, and the pressure is returned to atmospheric pressure again. After the impregnation, the electrode body with the exterior body open can be sealed while reducing the pressure.

[0089] [Alkaline metal doping process] In the alkali metal doping step, it is preferable to apply a voltage between the positive electrode precursor and the negative electrode, decompose the alkali metal compound preferably contained in the positive electrode precursor to release alkali metal ions, and reduce the alkali metal ions at the negative electrode, thereby pre-doping the alkali metal ions into the negative electrode active material layer. In the alkali metal doping step, gas such as CO2 is generated due to the oxidative decomposition of the alkali metal compound in the positive electrode precursor. Therefore, when applying a voltage, it is preferable to take a means for releasing the generated gas to the outside of the exterior body. Examples of this means include a method of applying a voltage with a part of the exterior body opened; a method of applying a voltage with a suitable gas release means such as a gas vent valve or a gas permeable film installed in advance on a part of the exterior body; and the like.

[0090] [Aging process] After the alkali metal doping step, it is preferable to perform aging on the electrode body. In the aging step, the solvent in the electrolyte is decomposed at the negative electrode, and a solid polymer coating permeable to alkali metal ions is formed on the surface of the negative electrode. The aging method is not particularly limited, but for example, a method of reacting the solvent in the electrolyte under a high temperature environment can be used.

[0091] [Gas removal process] After the aging process, it is preferable to perform degassing to reliably remove gas remaining in the electrolyte, the positive electrode, and the negative electrode. When gas remains in at least a part of the electrolyte, the positive electrode, and the negative electrode, ion conduction is inhibited, and the resistance of the obtained nonaqueous alkali metal storage element increases. The method of degassing is not particularly limited, but for example, a method of placing the electrode body in a reduced pressure chamber with the exterior body open and reducing the pressure in the chamber using a vacuum pump can be used. After degassing, the exterior body is sealed to close the exterior body, and a nonaqueous alkali metal storage element can be produced.

[0092] <<Uses of non-aqueous alkali metal storage elements>> A storage module can be produced by connecting a plurality of non-aqueous alkali metal storage elements in series or in parallel. The non-aqueous alkali metal storage element and the storage module can achieve both high input / output characteristics and safety at high temperatures. Therefore, they can be used in power regeneration assist systems, power load leveling systems, uninterruptible power supply systems, non-contact power supply systems, energy harvesting systems, storage systems, solar power generation storage systems, electric power steering systems, emergency power supply systems, in-wheel motor systems, idling stop systems, quick charging systems, smart grid systems, and the like. The storage system is preferably used for natural power generation such as solar power generation or wind power generation, the power load leveling system is preferably used for microgrids, and the uninterruptible power supply system is preferably used for factory production facilities, and the like. In the non-contact power supply system, the non-aqueous alkali metal storage element is preferably used for leveling voltage fluctuations such as microwave power transmission or electric field resonance and storing energy; and in the energy harvesting system, the non-aqueous alkali metal storage element is preferably used for using power generated by vibration power generation, and the like.

[0093] In the energy storage system, a plurality of nonaqueous alkali metal energy storage elements are connected in series or parallel to form a cell stack, or a nonaqueous alkali metal energy storage element is connected in series or parallel to a lead battery, a nickel-hydrogen battery, a lithium-ion secondary battery, or a fuel cell. Since the nonaqueous alkali metal energy storage element can achieve both high input / output characteristics and safety at high temperatures, it can be mounted on vehicles such as electric vehicles, plug-in hybrid vehicles, hybrid vehicles, and electric motorcycles. The above-described power regeneration assist system, electric power steering system, emergency power supply system, in-wheel motor system, idling stop system, or a combination thereof is suitably mounted on the vehicle. EXAMPLES

[0094] 《Example of producing oxidized coal (CO)》 Anthracite (Sanyo Kosho Co., Ltd., Vietnam) produced in a mortar was converted into oxidized coal (CO) using the Hummers method in a solution of NaNO3, H2SO4, KMnO4, and H2O2. The resulting mixture was washed three times with a 5% HCl solution and distilled water, and dried in a 50°C environment. The resulting CO powder was suspended in distilled water and irradiated with ultrasonic waves for 2 hours. The suspension was centrifuged to remove insoluble impurities, and the supernatant was collected to obtain a 1.5% by mass oxidized coal dispersion. The resulting sample was heat-treated in a calciner for 1 hour to prepare a sample for analysis.

[0095] [Analysis of oxidized coal] (Measuring the sheet size of oxidized coal using AFM) The sheet size of the oxidized coal samples for analysis obtained above was measured using an atomic force microscope (Bruker Digital Instruments Nanoscope V). The measurement results are shown in Figure 1. As shown in Figure 1, the oxidized coal had a plate-like shape with a width of about 30 nm and a height of about 1 nm.

[0096] (Measuring functional groups in oxidized coal using XPS) The oxidized coal sample for analysis obtained above was measured under the following conditions: X-ray source: monochromatic AlKα, X-ray beam diameter: 100 μmφ (25 W, 15 kV), pass energy: narrow scan: 58.70 eV, charge neutralization: yes, sweep number: narrow scan 10 times, energy step: narrow scan: 0.25 eV. Before the XPS measurement, the surface of the sample was cleaned by sputtering for 1 minute at an acceleration voltage of 1.0 kV in an area of ​​2 mm x 2 mm. The XPS measurement results showed that the carboxyl group content of the obtained oxidized coal was 16.7 atm%, and the epoxy group content was 6.3 atm%. The measurement results are shown in Figure 2.

[0097] 《Graphene oxide (GO) production example》 A graphene oxide dispersion was prepared in the same manner as above, except that graphene powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of anthracite. The obtained sample was heat-treated in a calciner for 1 hour to prepare a sample for analysis. When the XPS of the graphene oxide was measured in the same manner as above, the carboxyl group content was 5.1 atm% and the epoxy group content was 46.9 atm%. The results of the XPS measurement are shown in Figure 3.

[0098] <Production Example of Positive Electrode Precursor and Electrolyte> [Preparation of positive electrode active material] The crushed coconut shell carbonized material was placed in a small carbonization furnace and carbonized at 500°C for 3 hours under a nitrogen atmosphere to obtain a carbonized material. The obtained carbonized material was placed in an activation furnace, and steam heated in a preheating furnace was introduced into the activation furnace at 1 kg / h, and the temperature was raised to 900°C over 8 hours to activate the material. The activated carbon was removed and cooled under a nitrogen atmosphere to obtain activated carbon. The obtained activated activated carbon was washed with water for 10 hours, drained, dried for 10 hours in an electric dryer maintained at 115°C, and then pulverized in a ball mill for 1 hour to obtain activated carbon 1. The average particle size of activated carbon 1 was measured using a laser diffraction particle size distribution analyzer (SALD-2000J) manufactured by Shimadzu Corporation, and was found to be 5.5 μm. In addition, the pore distribution of activated carbon 1 was measured using a pore distribution analyzer (AUTOSORB-1 AS-1-MP) manufactured by Yuasa Ionics Corporation. As a result, the BET specific surface area was 2360m 2 / g, mesopore volume (V1) is 0.52 cm 3 / g, micropore volume (V2) is 0.88 cm 3 / g, V1 / V2=0.59.

[0099] [Production of positive electrode precursor 1] Activated carbon 1 was mixed at 55.4% by mass, CMC (carboxymethylcellulose) at 1.5% by mass, lithium carbonate at 31.1% by mass, carbon black (CB) at 2.4% by mass, acrylic latex (LTX) at 3.9% by mass, PVP (polyvinylpyrrolidone) at 1.8% by mass, and distilled water was mixed so that the mass ratio of the solid content was 15.0% by mass, and this was dispersed for 20 minutes at a rotation speed of 2000 rpm using a revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky Corporation to obtain a mixture. The obtained mixture was mixed with an oxidized coal dispersion so that the solid content ratio of the oxidized coal was 3.9% by mass, and the mixture was dispersed for 10 minutes at a rotation speed of 2,000 rpm to prepare a positive electrode coating liquid 1. The viscosity (ηb) and TI value of the obtained coating liquid were measured using an E-type viscometer TVE-35H manufactured by Toki Sangyo Co., Ltd. As a result, the viscosity (ηb) was 520 mPa·s and the TI value was 2.4. Using a doctor blade, positive electrode coating solution 1 was applied to one side of an aluminum foil with a thickness of 15 μm, and the applied coating was dried for 10 minutes on a hot plate heated to 50° C. After that, the coating was pressed using a roll press under conditions of a pressure of 6 kN / cm and a surface temperature of the press part of 25° C., thereby obtaining positive electrode precursor 1.

[0100] [Analysis of cathode precursor] The surface of the positive electrode active material layer of the positive electrode precursor 1 was coated with a gold film having a thickness of several nm by sputtering gold in a vacuum of 10 Pa. Then, an SEM image of the surface of the positive electrode active material layer was taken under atmospheric exposure under the conditions shown below. (SEM measurement conditions) Measurement equipment: Hitachi High-Technologies Corporation, field emission scanning electron microscope S-4700 Acceleration voltage: 1kV Emission current: 10μA ·Measurement magnification: 5,000x Detector: Secondary electron detector Electron beam incident angle: 90° When photographing, the brightness and contrast were adjusted so that there were no pixels in the SEM image that reached the maximum brightness value and the average brightness value was within the range of 40% to 60% of the maximum brightness value.

[0101] [Production Examples of Positive Electrode Precursors 2 to 10] Positive electrode precursors 2 to 6 were produced in the same manner as in [Production of positive electrode precursor 1], except that the amounts of each component used were adjusted as shown in Table 1.

[0102] Figure 4 is an SEM image of positive electrode precursor 1 taken at a magnification of 5,000 times. It was confirmed that the positive electrode active material (activated carbon 1) and the alkali metal compound (lithium carbonate) were uniformly coated with oxidized coal. Figure 5 is an SEM image of positive electrode precursor 5 taken at a magnification of 5,000 times. It was confirmed that there were no deposits on the positive electrode active material or the alkali metal compound. Figure 6 is an SEM image of positive electrode precursor 6 taken at a magnification of 5,000 times. It was confirmed that the positive electrode active material and the alkali metal compound were uniformly coated with graphene oxide, but because the graphene oxide sheet size was large, it also covered the voids in the positive electrode active material layer.

[0103] [Table 1]

[0104] [Preparation of electrolyte 1] A mixed solvent of ethylene carbonate (EC):ethyl methyl carbonate (EMC) = 33:67 (volume ratio) was used as the organic solvent, and electrolyte salts were dissolved therein so that the concentration ratio of LiPF6 and LiFSI was 1:1 and the total concentration was 1.2 mol / L, thereby obtaining nonaqueous electrolyte solution 1.

[0105] Example 1 <Manufacturing of single-pole cells> The obtained positive electrode precursor 1 was cut into one piece so that the positive electrode active material layer had a size of 4.4 cm x 9.4 cm, and vacuum dried at a temperature of 150 ° C. for 12 hours to obtain a working electrode. Then, a copper foil having a thickness of 10 μm was cut into one piece so that the size was 4.5 cm x 9.5 cm, and a metal lithium foil having a thickness of 50 μm and a size of 4.4 cm x 9.4 cm was attached to the copper foil to obtain a counter electrode. A polyethylene separator (manufactured by Asahi Kasei, thickness 15 μm) having a size of 4.7 cm x 9.8 cm and a glass filter having a size of 4.7 cm x 9.8 cm were prepared. Using these, the working electrode (positive electrode precursor 1), separator, glass filter, and counter electrode (metal lithium electrode) were laminated in this order so that the positive electrode active material layer and the metal lithium foil faced each other with the separator and glass filter sandwiched therebetween to obtain an electrode laminate. A positive electrode terminal and a negative electrode terminal were ultrasonically welded to the obtained electrode body, which was then placed in an exterior body made of an aluminum laminate packaging material, and the three sides including the electrode terminals were heat sealed.

[0106] [Injection, impregnation, sealing process] About 5.0 g of non-aqueous electrolyte 1 was injected into the exterior housing containing the electrode laminate under a dry air environment at atmospheric pressure, temperature 25°C, and dew point of -40°C or less. Next, the exterior housing containing the electrode laminate and the non-aqueous electrolyte was placed in a vacuum chamber, depressurized from atmospheric pressure to -87 kPa, then returned to atmospheric pressure, and left to stand for 5 minutes. Then, the process of depressurizing the exterior housing in the chamber from atmospheric pressure to -87 kPa and then returning to atmospheric pressure was repeated four times, and then left to stand for 15 minutes under atmospheric pressure. Through the above process, the non-aqueous electrolyte 1 was impregnated into the electrode laminate. Then, the electrode laminate impregnated with the non-aqueous electrolyte 1 was placed in a vacuum sealer, and the exterior housing was sealed by sealing at a pressure of 0.1 MPa at 180°C for 10 seconds in a state where the pressure was reduced to -95 kPa, to produce a single-electrode cell.

[0107] Evaluation of single-electrode cells [Capacitance measurement] The capacitance Qa (mAh / g) is a value obtained by the following method. First, the single-electrode cell is charged at a constant current of 3C in a thermostatic chamber set at 25°C until it reaches 4.0V, and then a constant voltage charge of 4.0V is applied for a total of 30 minutes. Next, the sampling interval is set to 1.0 second, and the capacitance (mAh) is obtained when the cell is discharged at a constant current of 1C to 2.0V. The capacitance Qa (mAh / g) is calculated by dividing the obtained capacitance by the weight of the positive electrode active material. The weight of the positive electrode active material can be calculated by subtracting the weight of the aluminum foil from the weight of the positive electrode precursor to calculate the weight of the positive electrode active material layer, and multiplying it by the composition ratio (mass%) of the positive electrode active material shown in Table 1.

[0108] [Measurement of decomposition capacity of alkali metal compounds] The decomposition capacity Qb (mAh) and Qc (mAh / g) of the alkali metal compound are values ​​obtained by the following method. First, the single-electrode cell is charged at a constant current of 3C in a thermostatic chamber set at 45°C until it reaches 4.5V, and then constant voltage charging is performed by applying a constant voltage of 4.5V for a total of 3 hours, and the decomposition capacity Qb (mAh) is obtained as the electric capacity flowing at a voltage of 4.2V or more. The value calculated by dividing the obtained electric capacity Qb by the weight of the alkali metal compound is taken as the decomposition capacity Qc (mAh / g). The weight of the alkali metal compound can be calculated by subtracting the weight of the aluminum foil from the weight of the positive electrode precursor to calculate the weight of the positive electrode active material layer, and multiplying it by the composition ratio (mass%) of the alkali metal compound shown in Table 1. Here, when lithium carbonate is used as the alkali metal compound, the decomposition efficiency of lithium carbonate can be calculated by dividing Qc by the theoretical capacity of lithium carbonate decomposition, 725mAh / g.

[0109] [Examples 2 to 8, Comparative Examples 1 and 2] A single-electrode cell was produced in the same manner as in Example 1, except that the positive electrode precursors were used as shown in Table 2.

[0110] [Table 2]

[0111] When the content A of oxidized coal is 0.5 mass% or more and 8.0 mass% or less, the capacitance Qa can be increased, and the decomposition capacity and decomposition efficiency of alkali metal compounds can be increased. When graphene oxide is used instead of oxidized coal, the surface of the positive electrode active material layer is excessively covered, which reduces the electrolyte retention and diffusibility, and it is believed that the decomposition capacity and decomposition efficiency of alkali metal compounds are reduced. In addition, it is believed that drying in a high-temperature environment at 150°C reduces graphene oxide and causes functional groups to disappear, so the capacitance does not increase and the decomposition capacity and decomposition efficiency of alkali metal compounds are reduced. [Industrial Applicability]

[0112] The positive electrode precursor of the present disclosure is preferably used as a lithium ion capacitor because the effect of the present invention is maximized, and can be suitably used as a non-aqueous alkali metal storage element used in a power regeneration system for a hybrid drive system of an automobile that requires high energy density, a power load leveling system for natural power generation such as solar power generation and wind power generation and a microgrid, an uninterruptible power supply system for a factory production facility, a non-contact power supply system for the purpose of leveling voltage fluctuations such as microwave transmission and electrolytic resonance and storing energy, and an energy harvesting system for the purpose of utilizing power generated by vibration power generation, etc. The lithium ion capacitor can be used, for example, to create a storage module by connecting multiple non-aqueous alkali metal storage elements in series or in parallel.

Claims

1. A positive electrode precursor comprising a positive electrode active material including a carbon material, oxidized coal, and an alkali metal compound other than the positive electrode active material, the positive electrode precursor includes a positive electrode current collector and a positive electrode active material layer including the positive electrode active material and the oxidized coal, the positive electrode active material layer being provided on one or both surfaces of the positive electrode current collector; at least a part of a surface of the positive electrode active material and at least a part of a surface of the alkali metal compound are coated with the oxidized coal, A positive electrode precursor, in which the oxidized coal has a carboxyl group functional group amount of 10.0 atm % or more and 26.0 atm % or less, and an epoxy group functional group amount of 0.1 atm % or more and 8.0 atm % or less, as measured by XPS (X-ray photoelectron spectroscopy).

2. 2. The positive electrode precursor according to claim 1, wherein a content of the oxidized coal contained in the positive electrode active material layer of the positive electrode precursor is 0.5 mass% or more and 8.0 mass% or less, based on a total mass of the positive electrode active material layer, and a content of the alkali metal compound is 20.0 mass% or more and 45.0 mass% or less, based on a total mass of the positive electrode active material layer.

3. The positive electrode precursor according to claim 1 or 2, wherein the sheet size of the oxidized coal measured by AFM (atomic force microscope) is 10 nm or more and less than 50 nm.

Citation Information

Patent Citations

  • High-performance lithium ion battery negative electrode material and preparation method thereof

    CN109428064A

  • Low-cost and high-rate graphene-based lithium iron phosphate electrode plate and preparation method thereof

    CN109698338A

  • Electric double layer capacitor

    JP2005093778A

  • Activated carbon for capacitor

    JP2005251941A

  • Positive electrode active material, manufacturing method for the same, and lithium ion capacitor including the same

    JP2012248826A